Factors associated with COVID-19 vaccine uptake among health professionals in Debre Markos town public health facilities, Northwest Ethiopia. - Michu Belay; Tilahun Degu Tsega; Muluye Molla; Muluken Teshome (Public Library of Science (PLoS), 2024)
Globally, the COVID-19 pandemic has significantly increased morbidity and mortality. Health professionals are at the frontline of COVID-19 pandemic exposure and are identified as a priority target group that needs to receive COVID-19 vaccines. Data on Ethiopian healthcare workers' use of the COVID-19 vaccine and associated factors, however, are scarce. Using a simple random sampling method, 398 health professionals were recruited through an institutional-based cross-sectional study design. Health professionals working in Debre Markos town public health facilities filled out a self-administered questionnaire that had been pretested to obtain the data. Then, the data were entered into Epi data version 4.2; and analyzed by SPSS 25. Descriptive statistics and multivariable logistic regression analysis were computed after model assumptions were checked. The adjusted odds ratio with 95% CI was calculated and statistical significance was declared at P-value < 0.05 after model adequacy was checked using the Hosmer-Lemeshow test. The uptake of the COVID-19 vaccine among health professionals was 61.56% (95% CI: 56.67%, 66.23%). Factors associated with the uptake of the COVID-19 vaccine were age > = 35 years (AOR: 4.39, 95% CI: 1.89, 10.19), having a higher income (>9056 Birr) (AOR: 1.79, 95% CI: 1.03, 3.10), who practiced COVID-19 Prevention methods (AOR: 2.39, 95% CI: 1.51, 3.77), Adulthood previous other immunization histories (AOR: 1.63, 95% CI: 1.15, 2.56) and having a chronic disease (AOR:1.90,95% CI: 1.07, 3.74). This study revealed that the uptake of the COVID-19 vaccine was low. Age > = 35 years, having a higher income, who practiced COVID-19 prevention methods, having adulthood previous immunization histories, and having chronic disease were statistically significantly identified factors for COVID-19 vaccine uptake. Therefore, policymakers and health managers should think about the requirement of immunization of healthcare workers and develop plans for administering the COVID-19 vaccine.